2018
DOI: 10.18632/aging.101609
|View full text |Cite
|
Sign up to set email alerts
|

Sirt1/Nrf2 pathway is involved in oocyte aging by regulating Cyclin B1

Abstract: Nuclear factor erythroid 2-related factor 2 (Nrf2) is capable of inducing a variety of biological effects, and the regulation of the Nrf2 signaling pathway is closely related to longevity. To find out whether the nuclear factor erythroid 2-related factor 2 (Nrf2) is involved in oocyte aging or not which may cause reduced female fertility, a series of biological methods was applied, including oocyte collection and culture, micro injection, RNA interference, western blotting, immunofluorescence and confocal micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 41 publications
0
35
0
Order By: Relevance
“…It has been reported that BDNF expression, Akt phosphorylation, and Nrf2 acetylation/deacetylation are mediated and critically controlled by SIRT1 (Pillai Vinodkumar et al, 2014;Ma et al, 2018). Based on these findings, we analyzed the effect of DDT on the expression of SIRT1 using western blot analysis.…”
Section: Ddt Protects Pc12 Cells Against Alcl 3 -Induced Oxidative Stmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that BDNF expression, Akt phosphorylation, and Nrf2 acetylation/deacetylation are mediated and critically controlled by SIRT1 (Pillai Vinodkumar et al, 2014;Ma et al, 2018). Based on these findings, we analyzed the effect of DDT on the expression of SIRT1 using western blot analysis.…”
Section: Ddt Protects Pc12 Cells Against Alcl 3 -Induced Oxidative Stmentioning
confidence: 99%
“…Sirtuin 1 (SIRT1) plays protective roles against several neurodegenerative diseases including Alzheimer's, Parkinson's, and motor neuron diseases (Guarente, 1999). Many studies have indicated that brain derived neurotrophic factor (BDNF) expression, Akt phosphorylation, and nuclear factor E2 related factor 2 (Nrf2) acetylation/deacetylation are mediated and critically controlled by SIRT1 (Pillai Vinodkumar et al, 2014;Ma et al, 2018). Moreover, the phosphatidylinositol 3-kinase (PI3K)/Akt signaling pathway plays a critical role in apoptosis (Zhu et al, 2016), which is important in maintaining mitochondrial integrity via the phosphorylation of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…However, whether SalB has a protective effect against sepsis-induced liver injury remains unknown. Sirtuin 1 (SIRT1), a nicotinamide adenine dinucleotide-dependent class III histone deacetylase, has been reported to play critical roles in various conditions, including oxidative stress, senescence and inflammation (14,15). Additionally, SIRT1 can activate peroxisome proliferator-activated receptor-γ co-activator 1α (PGC-1α), which is a key regulator in oxidative stress of the mitochondria (16).…”
Section: Introductionmentioning
confidence: 99%
“…to be responsible for the fertility loss of aged females (Ma et al, 2018;Yang et al, 2018;He et al, 2019;Nasheed Hamad Almohammed et al, 2020). Hence, dissection in greater depth of the possible interaction between ASB7 and these factors deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%